A Five-Gene Signature Associated With DNA Damage Repair Molecular Subtype Predict Overall Survival for Hepatocellular Carcinoma - Huo, Junyu; Fan, Xinyi; Qi, Bingxin; Sun, Peng (Frontiers in Genetics, 2022)
Background: DNA damage repair(DDR) is an important mechanism for the occurrence and development of hepatocellular carcinoma(HCC), but its impact on prognosis has not been fully understood. Materials and methods: A total of 840 HCC patients were included in our study, TCGA(n=370) and GSE14520(n=239) were merged into a large-sample training cohort(n=609). The training cohort was clustered into C1 and C2 based on prognostic DDR related genes, the differentially expressed genes(DEGs) between C1 and C2 were identified by the wilcoxon signed-rank test refered to criteria (|log2FC|≥1 and FDR< 0.05). The univariate Cox analysis was used to screen the prognostic related DEGs, and Lasso penalized Cox regression analysis were used to construct the risk score. The patients were clarified into high- and low-risk group based on the median risk score. ICGC cohort(n=231) were used for external validation of the risk score’s prognostic value. Results: The Kaplan–Meier survival analysis showed that high-risk group had a significantly reduced overall survival(OS) compared to the low-risk group in the three independent cohorts, and the time-dependent ROC curve showed that the five-gene(STMN1, PON1, PLOD2, MARCKSL1, and SPP1) risk score with a highly accuracy in predict OS. The patients with AFP >300ng/ml, tumor poor differentiation(grade 3-4), micro and marco vascular tumor invasion, advanced stage(AJCC III-IV, BCLC stage B-C, and CLIP score>2) exhibited a higher risk score. Subgroup survival analysis found that the risk score applicable to patients with different clinical characteristics. GO and KEGG functional enrichment analysis revealed that cell cycle, p53 signaling, TNF signaling related pathways were upregulated in high-risk group. The higher infiltration level of activated CD4 T cell, CD56 bright tural killer cell, plasmacytoid dendritic cell, and type 2 T helper cells were found to lead a unfavorable impact on the OS of HCC patients, and these four kinds of immune cells exhibited a higher infiltration level in the high-risk group. Conclusion: The five-gene risk score proposed in the research may provided new insights into the individualized evaluation of HCC prognosis.